Association of Tumor Necrosis Factor Alpha (TNF-α)-1031 Polymorphism with Chronic Infection of Patients with HCV - SH Baradaran Ghavami, (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Infection with the hepatitis C virus (HCV) is leading cause of chronic liver disease. Cytokines play a key role in the modulation of immune response. Different single-nucleotide polymorphisms (SNPs) in TNF-Alpha promoter region have been identified. The aim of this study was to investigate the association of TNF-α gene 1031 polymorphism with chronic hepatitis C patients.METHODS: This study is a case-control study. Genomic DNA of 119 HCV patients infected and 120 healthy controls were extracted and their genotypes were determined by PCR (Polymerase Chain Reaction) and RFLP (Restriction Fragment Length Polymorphism). FINDINGS: The frequency of TT, TC and CC genotypes was 88(73.9%), 31(26.1%) and (0.0%), respectively in case and it was 79(65.8%), 39(32.5%) and 2(1.7%), respectively in control (p=0.183). There was not a significant difference in genotype frequency between HCV patients and healthy control groups.CONCLUSION: The results of this study showed that there was no association between TNF-α gene 1031 polymorphism and chronic hepatitis C infection.